Transesophageal Echocardiograph Findings in Patients with Cardiovascular Disorders at Al-Thawrah General Hospital, Sana'a, Yemen - Al-Jaber, Noor-Aldeen; Thabet, Ahmed A. K.; Al-Hakeem, Manal; Al-Arashi, Manae; Sharaf, Abdulhakim; Al-Safadi, Essam (University of Science and Technology, Sana'a, 2015)
Objectives: To determine the frequency distribution of different cardiovascular disorders and to describe their associated morphological abnormalities by transesophageal echocardiography among patients referred to the Transesophageal Echocardiography Laboratory of Al-Thawrah General Hospital, Sanaa, in the period 2009- 2011. Methods: This was a retrospective descriptive study of 856 patients with suspected cardiovascular disorders and referred for transesophageal echocardiography over a two-year period. Data about patients sex, their refer- ral site and transesophageal echocardiography findings were collected and analyzed according to the type of cardiovascular disorders, valvular affections and lesions, complications and recommended treatments. Results: Of the 856 patients, 63.4% were females and 36.6% were males. The majority of patients diagnosed by transesophageal echocardiography (82.4%) were referred from outpatient departments. Rheumatic heart dis- ease was the most frequent cardiovascular disorder (87.1%), followed by tricuspid valve lesions (62.8%), of which 54% (329/606) were tricuspid regurgitation and 62.6% (114/182) were aortic valve regurgitation. Re- garding the type of valvular lesions detected, mitral valve disease was the most frequent, being found in 69.2% (214/309) of patients. Regarding the severity of valvular lesions, 73.1% (19/26) of mitral valve stenosis cases were severe while 83.3% (35/62) of aortic stenosis cases were mild. Moderate pulmonary hypertension was seen mostly secondary to rheumatic heart disease. The majority of cardiovascular disorder patients (33.6%; 284/844) were recommended for balloon mitral valvotomy. Mitral valve surgery was the most frequently per- formed surgical intervention for affected valves of patients with cardiovascular disorders; being used for the treatment of 31.4% (80/255) of valvular lesions. Conclusions: Transesophageal echocardiography revealed that rheumatic heart disease is the most frequent cardiovascular disorder among Yemeni patients and poses a major health problem. In addition, a high propor- tion of patients with cardiovascular disorders have valvular lesions of the mild degree that require surgical in- tervention.